Difficulties novice LIS researchers face while formulating a research topic. (September 2019) - Ameen, Kanwal; Batool, Syeda Hina; Naveed, Muhammad Asif
This study explored the difficulties faced by novice LIS researchers while formulating a topic. Qualitative research design was used to conduct this inquiry. Three focus-groups were conducted with research students enrolled in postgraduate programs at three LIS schools in the public-sector universities of Pakistan. The results indicated that lack of conceptual clarity, poor time management, and lacks of research culture were the major difficulties faced by the participants. These participants relied mainly on previously produced theses, research articles and their supervisors' help for conducting and producing their own work. The areas highlighted for improvement were primarily about the supervisors' role and the enhancement of the students' knowledge, training and practice during the course work. It is hoped that these results would not only be beneficial to the faculty involved in both supervision and teaching the research courses but also can play an instrumental role in streamlining topic formulation instructions in the curriculum. Despite being a case study of information professionals, the findings are most likely to be of wider interest for other subjects.